Life-cycle parameters of Copitarsia uncilata (Lepidoptera: Noctuidae) on three natural diets (2016)
This study describes the life cycle of Copitarsia uncilata Burgos and Leiva (Lepidoptera: Noctuidae) under laboratory conditions without photophase and a second experiment with photophase of 12 hours on three natural diets. The life cycle of C. uncilata was significantly shorter for females (76.46 ± 1.01 days, p=0.033) reared on alstroemeria (Alstroemeria sp.) diet without photophase, and for males (79.78 ± 0.36 days, p=0.046) reared on broccoli (Brassica oleracea italica), with photophase. The emergence of the adults was 100% and 80% from larvae fed on alstroemeria, 90.9% and 88.88% for individuals fed on broccoli, 86.2% and 50% for those fed on cauliflower (Brassica oleracea var. botrytis), without and with photophase respectively. The sex ratio (male:female) of individuals reared without photophase, evidenced a higher rate of females on alstroemeria (1:1.3), followed by cauliflower (1:0.6) and broccoli (1:0.5). In the experiment with photophase, the sex ratio was higher on alstroemeria (1:1.5), followed by cauliflower (1:0.9) and broccoli (1:0.6). As a conclusion, the most suitable diet for laboratory mass rearing in terms of life cycle parameters of C. uncilata is broccoli followed by alstroemeria and cauliflower.